2020
DOI: 10.3390/electronics9101732
|View full text |Cite
|
Sign up to set email alerts
|

In-Memory Data Anonymization Using Scalable and High Performance RDD Design

Abstract: Recent studies in data anonymization techniques have primarily focused on MapReduce. However, these existing MapReduce based approaches often suffer from many performance overheads due to their inappropriate use of data allocation, expensive disk I/O access and network transfer, and no support for iterative tasks. We propose “SparkDA” which is a new novel anonymization technique that is designed to take the full advantage of Spark platform to generate privacy-preserving anonymized dataset in the most efficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…Figure 12 presents the KLD values of our proposed subtree generalization implementation on Adult and Irish datasets. The KLD values increase with the increase of k-group size and are very close to the comparative approaches discussed [25,49].…”
Section: Kullback-leibler-divergence (Kld)supporting
confidence: 82%
See 4 more Smart Citations
“…Figure 12 presents the KLD values of our proposed subtree generalization implementation on Adult and Irish datasets. The KLD values increase with the increase of k-group size and are very close to the comparative approaches discussed [25,49].…”
Section: Kullback-leibler-divergence (Kld)supporting
confidence: 82%
“…We observed that the overall trends for the DM to the DM values observed in other similar approaches in [25,51]. As the k-group size increases, more records are part of an EC, and thus records are less distinguishable from each other.…”
Section: Discernibility Metric (Dm)mentioning
confidence: 54%
See 3 more Smart Citations